Enhancing copper recovery and electricity generation from wastewater using low-cost membrane-less microbial fuel cell with a carbonized clay cup as cathode. (20th February 2020) - Liu, Shu-Hui; Lai, Chi-Yung; Chang, Pei-Hsuan; Lin, Chi-Wen; Chen, Yu-Hsiu
Abstract: The recovery of low concentrations of copper in wastewater for industrial reuses meets the goals of circular economy. This work develops a modified clay cup (MCC) that can be used as a cathode in a membrane-less microbial fuel cell (ML-MFC) because of its porosity, adsorption and conductivity. The ML-MFC was then used to treat copper-containing wastewater and generate electricity. Cu 2+ is removed from wastewater and electricity produced primarily by the adsorption of Cu 2+ in the wastewater onto the MCC, reducing its inhibitory effects on biodegradation. Cu 2+ in wastewater can be reduced in an MFC to form copper-containing compounds on the surface of the MCC. Cu2 O can be used as a catalyst to modify the cathode to improve electricity production. In seven days ML-MFC with a power density of 113.7 mW/m 2 removed 96.5% of the Cu 2+ . At neutral pH, Cu2 O was observed on the surface of the MCC and modification of cathode reduced the internal resistance of the ML-MFC by 30%, increasing the output voltage. Cyclic voltammetry revealed a redox peak current at pH 7 that was 1.11–5.45 times under other conditions. This work demonstrates the feasibility of using an MCC cathode to increase the recovery of Cu 2+ and the generation of electricity by an MFC. Graphical abstract: Image 108200 Highlights: A clay cup (CC) that adsorbed Cu 2+ from wastewater to reduce biotoxicity. A cathode that was made of CC and molasses to increase power production. CuO2 that formed on the carbonized CC was used as a catalyst to modify the cathode. A neutral pH that reduced the internal resistance and improved copper recovery. An MCC cathode increased the recovery of Cu 2+ and the generation of electricity.